Caught in the ceasefire ; Cell Savvy ; To be confirmed [videorecording] - Lazaro, Cheche (Probe Productions, 1989)
Tackles military and NPA operations affecting civilians caught in crossfire in a rural area in Quezon province; characters drawn by Hanna Barbera and made in the Philippines by Filipino cartoons; importance of confirmation on the graft committed by Agrarian Reform Secretary Miriam Defensor Santiago.